Working in the methodological 'outfield': the case of Bourdieu and occupational therapy. Issue 2 (2nd April 2016) - Watson, Jo; Grenfell, Michael
Abstract : The article reports on a study of methodological innovation involving occupational therapy (OT) students in higher education (HE). It is based on an original project which examined the experiences and outcomes of non-traditional entrants to pre-registration OT education. A feature of the original project was the application of the epistemological and methodological approach of the French social theorist Pierre Bourdieu, most noticeably in exploring the way that social back ground ( habitus ) interacted with the educational ( field ) context in terms of experience and educational outcome. Bourdieu used a ranged of techniques – both qualitative and quantitative – in collecting and analysing data. In particular, he used multiple correspondence analysis (MCA), a type of geometric data analysis recognized as a powerful tool enabling the representation of social space and the situating of individuals within it with respect to a number of variables. The article considers methodological principles in comparing ethnographic, traditional statistics and MCA. We show how the original data were reanalysed according to MCA. The article compares the original analyses and findings with those based on MCA in order to explore its strength over the previous approach and the potential it has to cast light on various issues in HE.